Neonatal Hematological Abnormalities Associated with Maternal Pre-eclampsia at Birth - Asma Noreen; Falak Abro; Sana Dawood; Mehtab Hussain; Sobia Shah Alam; Uzma Arshad (ziauddin University, 2024)
Background: Pre-eclampsia (PE) can cause hematological abnormalities that can further exacerbate the existing morbidity in newborns. This study aimed to investigate neonatal hematological abnormalities associated with maternal pre-eclampsia at the time of birth. Methods: This cross-sectional was conducted from January 2023 to July 2023, involving 122 neonates born at the Department of Pediatric Medicine, Sohail Trust Hospital in Karachi, Pakistan. It analyzed neonates of either gender, aged from birth to 24 hours of life, and born to pre-eclamptic mothers, and their demographic details were recorded. At delivery, 2 ml of umbilical venous blood was collected by a trained pediatric nurse and then sent to the institutional laboratory. Hematological changes like leukopenia, thrombocytopenia, or neutropenia were noted. To assess the influence of various factors on hematological outcomes, chi-square tests were applied, with a significance threshold set at p<0.05. Results: In a total of 122 neonates, the mean age was 8.14±6.49 hours. The mean gestational age was 38.87±3.15 weeks. There were 68 (55.7%) neonates who were male. Low birth weight (LBW) was less than 2500 grams in 45 (36.9%) newborns. Thrombocytopenia, leukopenia, and neutropenia were identified in 32 (26.2%), 25 (20.5%), and 23 (18.9%) neonates respectively. Stratification of leukopenia concerning study variables revealed that gestational age and LBW had a significant association (p=0.0036, p=0.0072) with leukopenia. Moreover, neutropenia also had an association with LBW (p<0.0001). Conclusion: These findings underscore the importance of early hematological screening for neonates born to pre-eclamptic mothers to facilitate timely diagnosis and care.